2015
DOI: 10.1039/c5tb01184a
|View full text |Cite
|
Sign up to set email alerts
|

A dual-emission fluorescence-enhanced probe for imaging copper(ii) ions in lysosomes

Abstract: We have developed the first example of a fluorescence-enhanced and lysosome-targeted Cu 2+ probe (Lys-Cu) with unique dual-channel emissions. The new synthesized fluorescent probe Lys-Cu which contains two recognition sites with different sensoring mechanism to Cu 2+ , displays fluorescence-enhanced dual-channel emissions with fluorescence response to Cu 2+ under lysosome pH environment. Fluorescence imaging shows that Lys-Cu is membrane-permeable and suitable for visualization of Cu 2+ in lysosomes of living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 40 publications
(15 reference statements)
2
22
0
1
Order By: Relevance
“…After then, many Cu 2+ probes based on fluorescence intensity were synthesized [4,[9][10][11][12][13][14][15][16]. Although turn-on probes are more sensitive, a major limitation is that variations in the sample environment (pH, polarity, temperature, and so forth) might influence the fluorescence intensity measurements, due to the lack of background signal [17].…”
Section: Introductionmentioning
confidence: 99%
“…After then, many Cu 2+ probes based on fluorescence intensity were synthesized [4,[9][10][11][12][13][14][15][16]. Although turn-on probes are more sensitive, a major limitation is that variations in the sample environment (pH, polarity, temperature, and so forth) might influence the fluorescence intensity measurements, due to the lack of background signal [17].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we confirmed CD44-dependent copper endocytosis using a fluorescent probe designed to detect copper in lysosomes. Specifically, we used Lys-Cu, whose fluorescence selectively increases upon copper(II) binding 19 . Fluorescence microscopy revealed that a fluorescently labeled HA colocalized with this probe in aMDM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This observation was possibly due to the coordination between Cu 2+ and the 2,1,3‐benzoxadiazole N atom of 1O . Therefore, the formation of the complex 1O′ was proposed as shown in Figure according to the reported method …”
Section: Resultsmentioning
confidence: 99%